Ownership Concentration and IPO Underpricing: Evidence from the U.S. Stock Market - Jiang, Yanru (2012)
Underpricing for Initial Public Offering (IPO) is one of the hottest field financial researchers studied. Many existing theories have tried to explain the reason for underpricing. This study proposes that IPO is not a basic step for a firm raising new capital. It is also a conflict process of interest between different shareholders among large shareholders, controlling shareholders and small or outside shareholders. Because of the initial owners’ desire of controlling the firm after IPO, the ownership structure plays an important role in deciding the issuing price and initial return for the firm.